Procopius of Caesarea: A Case Study in Imperial Criticism - GILMER, James Michael (Byzantina Symmeikta, 2013)
This paper seeks to analyze the methods of Procopius of Caesarea and reconcile the apparent contradictions the historian presents in his treatment of the reign of the Emperor Justinian. To that end, the tone of each work is considered and compared to similar works of Late Antiquity. This paper will endeavor to demonstrate that the attitudes of Procopius toward the Emperor Justinian and many elements of his reign were universally hostile, veiled only by the conventions of the genres in which Procopius chose to write.